2019
DOI: 10.1556/066.2019.48.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Studying growth characteristics of yeast strains on vegetal fermentation media and with vitamin supplementation

Abstract: The primary purpose of these researches was to optimize single-cell protein (SCP) production process using Saccharomyces cerevisiae NCAIM Y.00200 and Kluyveromyces marxianus DSM 4908 strain, and then to analyse the changes in yield of single-cell protein fi nal product using vitamin supplementation. To determine these values, the total sugar content of the fermentation medium, and the protein content of the yeast was determined. During our work, a particular attention was paid to the change of sugar content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The role of nutrition in science and preventive medicine has already been demonstrated in practice and in a number of articles [13]. Outstanding among these are the research results achieved in fermentation biotechnology which revealed a significant innovation in the context of vitamin supplementation of yeast strains, among others [14]. In addition, foods that stimulate the immune system require increased attention due to the COVID-19 pandemic [15].…”
Section: Introductionmentioning
confidence: 99%
“…The role of nutrition in science and preventive medicine has already been demonstrated in practice and in a number of articles [13]. Outstanding among these are the research results achieved in fermentation biotechnology which revealed a significant innovation in the context of vitamin supplementation of yeast strains, among others [14]. In addition, foods that stimulate the immune system require increased attention due to the COVID-19 pandemic [15].…”
Section: Introductionmentioning
confidence: 99%